High‐resolution localized spatiotemporal encoding correlated spectra under inhomogeneous magnetic fields via asymmetrical gradient encoding/decoding. (12th December 2014) - Wei, Zhiliang; Lin, Liangjie; Wang, Chuchu; Yang, Jian; Liu, Guangcao; Zhong, Jianhui; Lin, Yanqin; Chen, Zhong
<x xml:space="preserve">Abstract</x> Applications of conventional localized nuclear magnetic resonance correlated spectroscopy are restrained by long acquisition times and poor performance under inhomogeneous magnetic fields. Here, a method that combines the spatiotemporal encoding technique with the localization technique and implements the encoding and decoding in unison with suitable asymmetrical gradients is proposed to obtain high‐resolution localized correlated spectra under inhomogeneous fields in greatly reduced times. Experiments on phantom solutions prove its insensitivity to linear field inhomogeneities along three orthogonal axes. Moreover, this method is applied to adipose study of marrow tissue with resolution improvements. The proposed method may offer promising perspectives for fast analyses of biological tissues. Copyright © 2014 John Wiley & Sons, Ltd.